2009
DOI: 10.1099/mic.0.034389-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-deficient Schizosaccharomyces pombe mutants undergo partial sporulation during nitrogen starvation

Abstract: Autophagy is triggered when organisms sense radical environmental changes, including nutritional starvation. During autophagy, cytoplasmic components, including organelles, are enclosed within autophagosomes and are degraded upon lysosome-vacuole fusion. In this study, we show that processing of GFP-tagged Atg8 can serve as a marker for autophagy in the fission yeast Schizosaccharomyces pombe. Using this marker, 13 Atg homologues were also found to be required for autophagy in fission yeast. In budding yeast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(120 citation statements)
references
References 51 publications
8
111
1
Order By: Relevance
“…1B, bottom). 46,47 These results strongly suggest that TORC2 remains active in fission yeast cells starved of nitrogen, consistent with the observation that the activity of TORC2 and Gad8 is essential for the cell cycle arrest and sexual development after nitrogen starvation. [14][15][16]19,48 The TORC2-Gad8 pathway is responsive to glucose It has been reported that the mitotic control under low glucose conditions is altered in a strain carrying the tor1-L2045D mutation of the TORC2 catalytic subunit.…”
Section: Torc2 Remains Active During Nitrogen Starvationsupporting
confidence: 84%
See 2 more Smart Citations
“…1B, bottom). 46,47 These results strongly suggest that TORC2 remains active in fission yeast cells starved of nitrogen, consistent with the observation that the activity of TORC2 and Gad8 is essential for the cell cycle arrest and sexual development after nitrogen starvation. [14][15][16]19,48 The TORC2-Gad8 pathway is responsive to glucose It has been reported that the mitotic control under low glucose conditions is altered in a strain carrying the tor1-L2045D mutation of the TORC2 catalytic subunit.…”
Section: Torc2 Remains Active During Nitrogen Starvationsupporting
confidence: 84%
“…46 Briefly, the GFP-Atg8 fusion protein, which was expressed exogenously under the control of the thiamine-repressible nmt1 promoter of pREP41 66 in the absence of thiamine, was examined in immunoblotting with antibodies against GFP for its autophagy-induced cleavage. Psk1 phosphorylation levels were analyzed as described before.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether organelle autophagy occurs in wild-type cells, we applied nitrogen starvation treatment, which is a trigger of general autophagy in S. pombe (Kohda et al, 2007;Mukaiyama et al, 2009;Sun et al, 2013), and monitored the subcellular localization of two organelle markers, an ER integral membrane protein Ost4 and a mitochondrial matrix protein Sdh2. We used Cpy1 as a vacuole lumen marker (Tabuchi et al, 1997).…”
Section: Organelle Autophagy Is Induced By Nitrogen Starvation In S mentioning
confidence: 99%
“…The special collection of research papers found in this issue spans a range of topics and organisms. Topics covered include primary metabolism (Heyland et al, 2009;Domin et al, 2009;Dawe et al, 2009) and its regulation (Teves et al, 2009;Vongsangnak et al, 2009;Wong et al, 2009), as well as the cellular and systems biology of key processes that underlie fungal growth (Bormann & Tudzynski, 2009;Hutchison et al, 2009;Etxebeste et al, 2009;Janus et al, 2009;Eisenman et al, 2009;Gale et al, 2009;Avanzo et al, 2009;Mukaiyama et al, 2009;Zara et al, 2009). Organisms include well-known model systems (Saccharomyces cerevisiae, Schizosaccharomyces pombe, Neurospora crassa, Aspergillus nidulans), human pathogens (Candida albicans, Cryptococcus neoformans), plant pathogens (Claviceps purpurea, Cryphonectria parasitica, Fusarium solani) and industrial producers (Penicllium chrysogenum).…”
mentioning
confidence: 99%